Foundations of education research : understanding theoretical components - Egbert, Joy (Routledge, 2020)
"The theoretical components of research are some of the most complicated and challenging aspects for new researchers to understand. While relevant methodologies are routinely covered by textbooks, the theory behind the practice can remain unnecessarily opaque. In seven concise chapters Foundations of Education Research defines, discusses, and presents applications for the central components of research in order to provide researchers with a common ground from which to work. Including conceptual framework, epistemology, paradigm, theory, theoretical framework, and methodology/method, this book gives students the tools they need to understand existing education research literature and to produce theoretically grounded work of their own. Beginning each chapter with perspectives from both novice and experienced researchers, this book is designed to help students achieve a deeper understanding of what is expected of them and ideas about how to achieve it. Guiding questions from both perspectives can assist researchers who are engaging with theory for the first time and those looking to improve their understanding of the fundamentals. Practice exercises and suggested reading lists at the end of each chapter offer students resources they can apply to their own research and thinking in concrete ways. A perfect accompaniment to standard research courses, this primer demystifies the jargon of education research in practical terms"--